All organic multiferroic magnetoelectric complexes with strong interfacial spin-dipole interaction - Yuying Yang (Nature Portfolio, 2021)
Abstract The organic magnetoelectric complexes are beneficial for the development on flexible magnetoelectric devices in the future. In this work, we fabricated all organic multiferroic ferromagnetic/ferroelectric complexes to study magnetoelectric coupling at room temperature. Under the stimulus of external magnetic field, the localization of charge inside organic ferromagnets will be enhanced to affect spin–dipole interaction at organic multiferroic interfaces, where overall ferroelectric polarization is tuned to present an organic magnetoelectric coupling. Moreover, the magnetoelectric coupling of the organic ferromagnetic/ferroelectric complex is tightly dependent on incident light intensity. Decreasing light intensity, the dominated interfacial interaction will switch from spin–dipole to dipole–dipole interaction, which leads to the magnetoelectric coefficient changing from positive to negative in organic multiferroic magnetoelectric complexes.